2020
DOI: 10.3847/1538-4357/ab5af7
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Isotopic Constraints on the Origin of the Ureilite Parent Body

Abstract: We report on the mass-independent Cr isotope compositions of 11 main group ureilites and an ureilitic trachyandesite (ALM-A). The 54 Cr/ 52 Cr ratios for main group ureilites vary from −1.06±0.04 to −0.78±0.05 and averaged at −0.91±0.15 (2SD, N=18) including the data from literature. We argue that this variation reflects primitive mantle heterogeneities within the ureilite parent body (UPB). As such, this body did not experience a global-scale magma ocean, which is consistent with heterogeneous O isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 100 publications
(231 reference statements)
3
39
0
Order By: Relevance
“…If this is true, and if the UPB accreted relatively late (1.4–1.7 Ma after CAIs) as suggested by Budde et al (2015), then the UPB would have accreted within the orbit of proto‐Jupiter together with the other NC parent bodies. However, the accretion time of the UPB is still debated and Van Kooten et al (2017) and Zhu et al (2020) argued that the UPB was partly differentiated earlier than 1 Ma after CAIs (and as early as 0.6 Ma ΔCAIs), an older age compatible with the thermal evolution models of Wilson et al (2008) and Goodrich et al (2015). Based on a presumed relationship between Si isotopes and the Mg/Si ratio of parent bodies, Dauphas et al (2015) calculated a value of 1.00 ± 0.08 for the UPB, but the uncertainty overlaps with both carbonaceous and ordinary chondrites.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…If this is true, and if the UPB accreted relatively late (1.4–1.7 Ma after CAIs) as suggested by Budde et al (2015), then the UPB would have accreted within the orbit of proto‐Jupiter together with the other NC parent bodies. However, the accretion time of the UPB is still debated and Van Kooten et al (2017) and Zhu et al (2020) argued that the UPB was partly differentiated earlier than 1 Ma after CAIs (and as early as 0.6 Ma ΔCAIs), an older age compatible with the thermal evolution models of Wilson et al (2008) and Goodrich et al (2015). Based on a presumed relationship between Si isotopes and the Mg/Si ratio of parent bodies, Dauphas et al (2015) calculated a value of 1.00 ± 0.08 for the UPB, but the uncertainty overlaps with both carbonaceous and ordinary chondrites.…”
Section: Discussionmentioning
confidence: 96%
“…There is little doubt that the UPB accreted from isotopically heterogeneous materials. The fact that C (Barrat et al 2017), Cr (Zhu et al 2020), and O isotopes (Clayton and Mayeda 1988) all correlate with the Mg# of silicates suggests that the intrinsic f O 2 of ureilites was at least partly inherited from the precursor chondritic materials. The origin of the intrinsic f O 2 of meteorite parent bodies is an active area of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-lived radionuclide 53 Mn, with a half-life of 3.7 ± 0.2 Myrs (Holden, 1990), decays to 53 Cr and was present in the early Solar System (Lugmair and Shukolyukov, 1998). Therefore, the 53 Mn-53 Cr decay system is a useful chronometer to date early Solar System events such as chondrule (precursor) formation (Nyquist et al, 2001;Yamashita et al, 2010;Zhu et al, 2019a;Zhu et al, 2020a), differentiation of planets/asteroids (Lugmair and Shukolyukov, 1998;Trinquier et al, 2008b;Wadhwa et al, 2003;Yamakawa et al, 2010;Zhu et al, 2019b;Zhu et al, 2020b), as well as the aqueous alteration (Fujiya et al, 2012;Fujiya et al, 2013) and possibly the metamorphic processes in chondrite parent bodies (Trinquier et al, 2008b;Go ¨pel et al, 2015). Furthermore, previous Cr isotope measurements have suggested that the various carbonaceous chondrite (CC) groups define a bulk isochron with a slope defining an initial 53 Mn/ 55 Mn ratio of (8.5 ± 1.5) Â 10 -6 , which was used to suggest that a volatile fractionation in the solar nebular occurred as early as 4568.6 ± 1.1 Ma Lugmair 2006, Moynier et al 2007) when the date is anchored to the U isotope corrected age of the D'Orbigny angrite (Amelin, 2008;Brennecka and Wadhwa, 2012;Glavin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Δ 17 O values of a few mg silicate samples (approximately 1 mm 3 ) can be measured by a laser fluorination system with an analytical precision of less than 0.01‰, enough to distinguish between different meteorite groups (e.g., Herwartz et al 2014 ; Young et al 2016 ; Greenwood et al 2018 ). The Cr isotopic composition of extraterrestrial materials is usually measured by ICP-MS or Thermal Ionization Mass Spectrometry (TIMS) (e.g., Mougel et al 2018 ; Zhu et al 2020 ), while Ti isotopic composition is measured by ICP-MS (e.g., Trinquier et al 2009 ). The mass of Cr and Ti required for such measurements at high precision is roughly around 1 μg, which represent a few mg of samples whichever it is chondritic (e.g., ~ 3000 ppm Cr and 500 ppm Ti) or differentiated like shergottites (~ 700 ppm Cr and 6000 ppm Ti) (Brown et al 2000 ; Taylor et al 2002 ; Hibiya et al 2019 ).…”
Section: Sample Analysesmentioning
confidence: 99%